Phase behavior and material properties of hollow nanoparticles - Schwarz, Ulrich S.; Safran, Samuel (Physical review. E, Statistical, nonlinear, and soft matter physics, 2000)
Effective pair potentials for hollow nanoparticles such as those made from carbon (fullerenes) or metal dichalcogenides (inorganic fullerenes) consist of a hard core repulsion and a deep, but short-ranged, van der Waals attraction. We investigate them for single-walled and multiwalled nanoparticles and show that in both cases, in the limit of large radii the interaction range scales inversely with the radius R, while the well depth scales linearly with R. We predict the values of the radius R and the wall thickness h at which the gas-liquid coexistence disappears from the phase diagram. We also discuss unusual material properties of the solid, which include a large heat of sublimation and a small surface energy.